The status of apoproteins b100 and a1 in type 2 diabetes in Erbil city - Salih Khalnd, Avin; Bilal Abbas , Leweza (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Type 2 diabetes mellitus (T2DM) originates from the body’s incapacity to react to insulin. Hypoglycemic medications and lifestyle modifications can help control it. The aim of this study was to compare the serum Apolipoprotein B100/Apolipoprotein A1 Ratio (ApoB100/ApoA1) between T2DM patients and controls. Methods: This case-control study was conducted in the Galiawa Teaching Center for Diabetes and Endocrinology in Erbil City from October to December 2024. The blood samples were taken from 45 patients with T2DM and 45 healthy control subjects. Two types of tubes were used to collect blood samples: one for serum separation (gel tube) and another for plasma (tri-potassium ethylene diamine tetra acetic acid) (K3EDTA) tube. The samples have been left at room temperature for fifteen minutes and then put in a centrifuge for ten minutes at 4000 rpm to get the serum of the blood. The separated serum was subjected to laboratory analysis to analyze the biochemical tests (ApoA1, ApoB100, fasting serum glucose, hemoglobin A1C (HbA1C), and lipid profile). Results: Based on the research findings, diabetic patients had substantially higher levels of serum glucose, HbA1C, lipid profiles, and ApoB100/ApoA1 ratio than the healthy individuals. The case group had a mean serum ratio ApoB100/ApoA1 of (0.84±0.06), while the control group had a ratio of (0.66±0.02) g/L (P = 0.037). While HbA1C and serum glucose with all lipid profile results were significantly higher in T2DM than the control group, high-density lipoprotein (HDL) was lower in T2DM. Conclusion: The study found that patients with T2DM had a high ApoB100/ApoA1 ratio. Compared to the control group.